Tax evasion under behavioral structures - Gabriela S. Pantoja; Rodrigo S. Penaloza (EconomiA, 2014)
We study the strategic interactions between the fiscal authority and the taxpayer regarding tax evasion and auditing. We fit this interaction into a Bayesian game and introduce the concept of behavioral consistency, which helps reducing the number of available strategies and models the stylized fact according to which the choice to evade is subject to behavioral patterns. – – Neste trabalho estudamos as interaç\~oes entre o contribuinte e o fisco no que diz respeito à evas\~ao fiscal e à auditoria. Para isso, construímos um jogo bayesiano e introduzimos a hipótese de consistência comportamental, que reduz o conjunto de estratégias e modela o fato estilizado segundo o qual a evas\~ao ou n\~ao evas\~ao está sujeita a padr\~oes comportamentais.
Keywords: H26; D82; C72; 330; Tax evasion; Bayesian equilibrium; Behavioral consistency